The Relevance of Buddhayana Principles to Religious Moderation in Indonesia - Suharno Suharno; Lasiyo Lasiyo; Hastanti Widy Nugroho (UIN Sunan Gunung Djati Bandung, 2026)
In order to preserve national integrity, religious moderation is essential. Buddhist teachings, like those of all other religions in Indonesia, support religious moderation. Buddhayana is one of the scholastic schools of Buddhism in Indonesia. The purpose of this study is to investigate the applicability of Buddhayana ideas to Indonesian religious moderation. This study's methodology is a review of the literature. The study's findings suggest that certain Buddhist teachings align with the markers of religious moderation. The Kutadanta Sutta contains Buddhist teachings about national commitment. The Buddha exemplifies tolerance in the Upali Sutta by counselling devotees like Upali to carefully consider new views before changing, always showing respect for their prior affiliations. According to the Buddha, every human being develops non-violence based on their brahmavihara, which includes metta, karuna, mudita, and upekkha. The Buddha teaches accommodation of local culture in the Sigalovada Sutta, which says that proper understanding is the foundation for both openness and the preservation of local culture. The tenets of Buddhayana, which include a non-sectarian, inclusive, pluralistic, universal mindset and faith in Sanghayang Adi Buddha, are consistent with the practice of religious moderation.